Les trois dimensions de la signifiance dans une approche anthropo-philosophique, interlocutive et empirique de la personne en éducation - Marie-Louise Martinez; Tommy Terraz (Université de Provence, 2017)
The three components of meaning described by Morris (1964) from Peirce, used in linguistics and didactics, are redefined in philosophy by Francis Jacques (1987) as the three dimensions = reference, difference, communicability set up aprioristically to the status conditions of possibility of signifiance and textuality. In the article, after having presented the issues of the categorization of the three dimensions that makes it possible to differentiate texts, we evoke the transposition carried out from the a priori Jacquerian epistemological approach towards an empirical approach. Such an approach, at the crossroads of the philosophy of education and the pragmatic and interlocutory philosophy of language and person, beyond the observation of the difference of the texts makes it possible to identify the co-construction of personal identities in the interlocutory exchange. The passage is justified in its opportunity thanks to the question of the integration of the formerly excluded third that the transcendental pragmatics of Jacques (1982, 1985) allows to ask but not to solve. On the epistemological level, the empirical approach manifests the presence of the third which transcendental formalism crowds out, as Michel Serres (1966) sees. The theoretical contribution for both education professionals and researchers, who can observe without reifying people, is considerable. On the methodological level we can objectify the emergence of the person in the linguistic marks of the educational and professional interlocutive relationship.